2016
DOI: 10.3892/etm.2016.3761
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic twins with infantile neuroaxonal dystrophy: A case report and literature review

Abstract: Abstract. Infantile neuroaxonal dystrophy (INAD) is a rare neurodegenerative disease with early onset. PLA2G6 gene mutations have been identified in the majority individuals with INAD. In future, molecular diagnosis of INAD will replace the invasive biopsies used previously. In the present report, monozygotic male twins with INAD were referred The Children

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As costimulatory signal molecules, CD80 and CD86 widely exist on the surface of DCs and NK cells and participate in cellular immunity. CD80 can promote T cells to differentiate into Th1, while CD86 can induce Th2-mediated humoral immunity, which makes Th1/Th2 unbalanced, thus enlarging abnormal immune response [ 18 ]. In vitro experiments showed that [ 19 ], monoclonal antibody blocked CD80 and CD86 molecules and blocked CD28/B7 pathway, while cytotoxic T cell associated antigen 4 could bind to B7, thus inhibiting the proliferation of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…As costimulatory signal molecules, CD80 and CD86 widely exist on the surface of DCs and NK cells and participate in cellular immunity. CD80 can promote T cells to differentiate into Th1, while CD86 can induce Th2-mediated humoral immunity, which makes Th1/Th2 unbalanced, thus enlarging abnormal immune response [ 18 ]. In vitro experiments showed that [ 19 ], monoclonal antibody blocked CD80 and CD86 molecules and blocked CD28/B7 pathway, while cytotoxic T cell associated antigen 4 could bind to B7, thus inhibiting the proliferation of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some MRIs also show thin optic chiasma, signal hyperintensity of the dentate nuclei and white matter, and cerebral cortical atrophy (32). An electromyography (EMG) also shows denervation in the peripheral nervous system (29), and an EEG can reveal the widespread high-amplitude fast activity at 16–22 Hz after 2 years of age (33). Visual evoked potentials (VEPs) and electroretinograms (ERGs) appear normal in the early stage of the disease, followed by an increase in abnormal signs over time (27).…”
Section: The Clinical Phenotypes Of Pla2g6-associated Neurodegenerationmentioning
confidence: 99%
“…The deafness may be associated with the mutations of PLA2G6 or have other causes, which requires further study. According to the 4 studies available that report on PLA2G6-associated neurodegeneration in China ( 19 – 22 ), 29 different mutations were identified in 28 Chinese pediatric patients with PLA2G6-associated neurodegeneration, of which 14 were novel. However, it remains to be clarified whether and how PLA2G6 mutations lead to hearing loss.…”
Section: Discussionmentioning
confidence: 99%